Isopropanol exposure: environmental and biological monitoring in a printing works. Issue 2 (May 1983) - Brugnone, F; Perbellini, L; Apostoli, P; Bellomi, M; Caretta, D
Abstract : Occupational exposure to isopropanol was studied in 12 workers by testing environmental air, alveolar air, venous blood, and urine during their work shift. Isopropanol, which ranged in environmental air between 7 and 645 mg/m3, was detected in alveolar air, where it ranged between 4 and 437 mg/m3, but not in blood or in urine. Alveolar isopropanol concentration (Ca) was significantly correlated with environmental isopropanol concentration (Ci) at any time of exposure. The value of the arithmetical Ca/ci ratio was 0.418 (SD 0.101). Acetone, which is a metabolite of isopropanol, was found in alveolar air, blood, and urine in concentrations that were higher during exposure than before. Alveolar and blood acetone concentrations were highly correlated with alveolar isopropanol concentrations at any time during exposure. Acetone ranged between 0.76 and 15.6 mg/l in blood, between 4 and 93 micrograms/l in alveolar air, and between 0.85 and 53.7 mg/l in urine. Alveolar (Ca) and blood (Cb) acetone concentrations were highly correlated (r = 0.67), with a Cb/Ca ratio of 101. Alveolar isopropanol uptake ranged between 0.03 and 6.8 mg/min and was highly correlated with environmental isopropanol concentration (r = 0.92). During exposure, acetone eliminated by the lungs ranged between 20 and 273 mg in seven hours and in urine between 0.3 and 9.6 mg in seven hours. Acetonuria was higher the next morning than at the end of exposure.